PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Partasiwi, Nurashri; Kirana, Arinta Rara; Arga, Kharisma Idola; Pratama, Elvandri Yogi (Lentera: Jurnal Ilmiah Kependidikan, 2021)
This study aims to determine the effect of the cooperative learning model type GI (Group Investigation) on students' mathematical communication skills. This research is a quantitative research with a type of quasi-experimental research. The population in this study were all students of class X TO at SMK Negeri 5 Bandar Lampung even semester of the 2020-2021 academic year, amounting to 179 students and sampling using cluster random sampling technique so that two classes were obtained as the research sample, namely class X TO 4 as the experimental class. as many as 36 students and class X TO 5 as the control class as well as 36 students. Data were collected through tests of mathematical communication skills in the form of essay tests. Based on the t test conducted, it was obtained t count > t table which was 16.50 > 1.69, which means that there was a significant influence on the cooperative learning model type GI (Group Investigation) on students' mathematical communication skills in class X TO SMK Negeri 5 Bandar Lampung Even Semester of The 2020-2021 Academic Year.